Beliefs and Science of the Sasquatch / Bigfoot: Examples of Vernacular (Re)search - Tita, Michele (Tautosakos darbai, 2025)
In his 1977 article, folklorist David Hufford argued against the epistemological authority of scientific knowledge over beliefs. In support of his argument, Hufford mentioned the American humanlike creature named Sasquatch, or Bigfoot; its existence has not been proven scientifically but should be trusted, in Hufford’s opinion, since it has been widely historically claimed and believed in. Attempts to explain the evolutionary origins or to prove the existence of the Sasquatch scientifically include field expeditions in search of the creature, popular science writings, and museum work. These efforts are examples of vernacular (re)search, conducted autonomously from academic and scientific institutions. Nevertheless, many vernacular (re)searchers strive to maintain scientific rigor in their activities and interpretations, and to adjust their (re)search to the framework of science. The given article offers examples of interpretations and vernacular studies of the Sasquatch, a creature that keeps challenging the dichotomy between beliefs and (scientific) knowledge.